2023
DOI: 10.3390/ijms241310723
|View full text |Cite
|
Sign up to set email alerts
|

Monocytes in the Characterization of Pain in Palliative Patients with Severe Dementia—A Pilot Study

Abstract: In assessing and managing pain, when obtaining a self-report is impossible, therapeutic decision-making becomes more challenging. This study aimed to investigate whether monocytes and some membrane monocyte proteins, identified as a cluster of differentiation (CD), could be potential non-invasive peripheral biomarkers in identifying and characterizing pain in patients with severe dementia. We used 53 blood samples from non-oncological palliative patients, 44 patients with pain (38 of whom had dementia) and 0 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Ribeiro et al [20] have reported on the difficulties of assessing and managing pain, under conditions when obtaining a self-report is impossible and therapeutic decision-making becomes more challenging. On the basis of their experimental data, they proposed monocytes and some membrane monocyte proteins, identified as a cluster of differentiation (CD), as potential, non-invasive, peripheral biomarkers in identifying and characterizing pain in patients with severe dementia.…”
mentioning
confidence: 99%
“…Ribeiro et al [20] have reported on the difficulties of assessing and managing pain, under conditions when obtaining a self-report is impossible and therapeutic decision-making becomes more challenging. On the basis of their experimental data, they proposed monocytes and some membrane monocyte proteins, identified as a cluster of differentiation (CD), as potential, non-invasive, peripheral biomarkers in identifying and characterizing pain in patients with severe dementia.…”
mentioning
confidence: 99%